PENDEKATAN MAQASHID SYARIAH DALAM KEGIATAN SOSIAL DAN EKONOMI PADA PERSPEKTIF PRAKTIK FIQH MUAMALAH KONTEMPORER - Nadia Saphira; Fauziyah Mulyana Putri; Muhammad Miqdad; Muhammad Jalil (Media Riset Bisnis Manajemen Akuntansi, 2025)
This paper aims to examine the application of maqashid sharia in the field of muamalah jurisprudence, emphasizing the importance of the objectives of sharia in providing normative guidance that can be used to assess and formulate muamalah laws in order to achieve the welfare of the community. This research employs a qualitative analysis method with a literature review approach involving various relevant literary references. The findings reveal that the application of maqashid sharia not only serves to protect property (hifz al-mal) but also to promote social values such as justice, welfare, and the protection of individual rights. Furthermore, this research identifies that the implementation of maqashid sharia in a modern context can enhance public trust in the sharia financial system, as well as provide solutions to issues encountered in current muamalah practices. Keywords : Economic, Fiqh muamalah, Maqashid sharia, Sharia financial system, Social values